Cooperative component of the import substitution strategy of Ukraine - KUDYRKO, Liudmyla; SAMSONOVA, Liliia (Ius Modernum, 2019)
The thesis is based on the fact that in conditions of high level of the national economy dependence on imports of finished goods and intermediate goods, the mechanism, which is aimed to promote improvement of the structure and quality of international economic relations with participation of national business, is the activation of international cooperation ties. The characteristics of the import dependence level of some branches in Ukraine have been given and the prospects of solving the import dependence problem have been solved through the implementation of balanced import substitution strategy, part of which is the development of international inter- and intra-sectoral cooperation.